The wealth and saving of UK families on the eve of the crisis - Thomas F. Crossley; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2010)
This report looks at the level of wealth and the rate of saving of households in the UK on the eve of the global economic crisis. Our approach is to use microdata sources to look at the extent to which wealth holdings and saving rates vary across individuals. We use the British Household Panel Survey (BHPS) to study household wealth, and we use both the BHPS and the Expenditure and Food Survey (EFS) to study household saving. We emphasise that the vast majority of household wealth is held in an illiquid form.
Keywords: 330